SISTEM INFORMASI TAMBAHAN PENGHASILAN PEGAWAI PADA RUMAH SAKIT UMUM MOKOYURLI KABUPATEN BUOL - Idris, Nur Oktavin; Farid, F.; Gafur, Abdul (Journal Of Software Engineering And Communication, 2023)
The Additional Employee Income (TPP) allowance is given by the government to Civil Servants (PNS) who work at government institutions and are eligible during the assessment period. The giving aims to enhance performance, improve discipline, and increase public and apparatus performance. TPP processing calls for accurate reporting and calculation concerning TPP recipients, especially from RSUD Mokoyurli Buol. And yet, the processing still leverages Microsoft Excel, hampering easy data inputting on work discipline. In addition, manual reporting causes those concerned to find the entailed information longer. These issues breed ineffective and inefficient data processing. Accordingly, this research focuses on designing an information system which allows efficient TPP processing, performance productivity reporting, and TPP recapitulation on a monthly basis. The Android-based system enables civil servants to self-report their attendance using smartphones. The method used is Research and Development (R&D). Results are expected to help input data on TPP, report attendance, prevent piling up reporting, and bring about easier access to information